Effects of matrix viscosity on morphological and rheological properties and the electrical percolation threshold in graphene/epoxy nanocomposites - A. Alipour; T. Giffney; R. Lin; K. Jayaraman (eXPRESS Polymer Letters)
Graphene nano-platelets (GNPs) can substantially improve the performance of epoxy resin, but improving effects are highly dependent on GNP dispersion uniformity in the matrix. The aim of the current study is to explore the influence of matrix viscosity on the dispersion of GNPs. Thus, epoxy matrix with three disparate viscosities was reinforced with GNPs varying from 0 to 3 wt%, and the influence of matrix viscosity on dispersion uniformity and thus properties of composites were identified. Significant differences in rheological and electrical percolation thresholds were found with a change in the matrix viscosity. The lowest rheological percolation threshold (0.3 vol%) and electrical percolation threshold (0.53 vol%) were always observed in specimens based on a low viscosity matrix. X-ray Diffraction (XRD) results also showed that lower viscosity resulted in better GNPs distribution. The visual state of GNPs dispersion with a change in matrix viscosity was also evaluated through Scanning Electron Microscopy (SEM) and optical microscopy. Optical microscopy images confirmed that while the GNP agglomeration diameter is 42.3 µm in high-viscosity resin, it markedly decreased to 15.1 µm by using low viscosity resin. Transmission Electron Microscopy (TEM) quantitative measurements pertaining to the number of GNP stacked layers also showed that when a low viscosity matrix was used, only 11 layers stack on each other and form thinner clusters compared to 13 and 39 layers in medium and high ones.